2020
DOI: 10.47312/aar.v5i01.184
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Risk-Based Review Plan for Accrual Based Local Government Financial Reports

Abstract: <p><em>The application of Accrual-Based Government Accounting Standards (SAP) since 2015 still causes problems including misstatement in Local Government Financial Reports (LKPD). The role of the Inspectorate in minimizing these problems is manifested in conducting a review of LKPD. Preliminary research shows that the implementation of LKPD review in Bandung District has not been effective in detecting financial statement misstatements. This study aims to evaluate and design a risk-based review pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The results of this study are in line with previous research who concluded that data reconciliation has a significant positive effect on the quality of financial reports (Cahyani, 2023;Choi et al, 2013;Pizzini et al, 2015;Wahyuni et al, 2018). Reconciliation competence has a positive and significant effect on the quality of the Nias Regency Regional Government's financial reports while previous research results show that internal and external reconciliations have a positive and significant effect on the quality of financial reports at BPS (Chairunnisa & Pamungkas, 2020;Masnila et al, 2021).…”
Section: Effect Of Data Reconcilliation On the Quality Of Financial R...supporting
confidence: 90%
“…The results of this study are in line with previous research who concluded that data reconciliation has a significant positive effect on the quality of financial reports (Cahyani, 2023;Choi et al, 2013;Pizzini et al, 2015;Wahyuni et al, 2018). Reconciliation competence has a positive and significant effect on the quality of the Nias Regency Regional Government's financial reports while previous research results show that internal and external reconciliations have a positive and significant effect on the quality of financial reports at BPS (Chairunnisa & Pamungkas, 2020;Masnila et al, 2021).…”
Section: Effect Of Data Reconcilliation On the Quality Of Financial R...supporting
confidence: 90%